Manajemen Pengetahuan dan Daya Saing Organisasi: Sebuah Review Era Persaingan Berbasis Pengetahuan Sumber Daya Manusia dan Manusi Bersumber Daya dalam Organisasi Aplikasi Tiga Komponen Komitmen Allen dan Meyer dalam Konteks Hubungan Pelanggan dengan - Lina Anatan; Meily Margaretha (Jurnal Manajemen Maranatha, 2007)
This article discusses the impact of knowledge management to improve organizational competitiveness. As business enter knowledge-based economy era, organizations have to cope with challenges of technological sophistication and global competition, and the importance of knowledge as source of organizational competitive advantage. Employee began to experience work differently with a new array of rules, expectation, and condition of employment predicted on uncertainty and chaos. In order to respond these challenges, organizations as business performer require the role of high quality and competence human resource to response the development and changes of business environment. The implementation of management and investment in human resource as one of competitive advantage sources are crucial. It may be due to human resource is subject or performer in the enterprise operational activity that use and manage other resources. To create knowledge for individual and to get more benefit from knowledge, knowledge has to be managed through knowledge management. Knowledge management defined as the process of managing knowledge. In other words, t is a structured coordination for managing knowledge effectively. Through knowledge management, organization will be able to implement organizational and self learning and to manage professional intellect.